Exploring the longitudinal impacts of academic stress and lifestyle factors among Chinese students - Wang Han; Ali Altalbe; Nadia Rehman; Shazia Rehman; Samantha Sharma (Taylor & Francis Group, 2024)
Background Several cross-sectional and longitudinal investigations have demonstrated a robust association between academic stress, physical activity, mental health history, and time management skills. However, the existing literature exhibits inconsistencies in the relationship between academic stress and its predictive effects on physical activity and mental health history. In addition, there is a scarcity of scholarly research that concentrates on the significance of time management skills within this particular context. Furthermore, limited research has investigated these variables' longitudinal associations and causal pathways. Therefore, the present research explores the longitudinal relationships among academic stress, physical activity, mental health history, and time management skills among university students.Methods The data were gathered from Wuhan University, China, employing a two-wave longitudinal survey methodology with an annual interval. A cohort of 980 university-level students engaged in the completion of questionnaires, which encompassed measures of academic stress via the Educational Stress Scale for Adolescents (ESSA), physical activity ascertained through Cho's five-item questionnaire, mental health history assessed by the Kessler Psychological Distress Scale, and time management skills evaluated using the Time Management Behaviour Scale (TMBS). Subsequently, a cross-lagged path model was utilised to examine the prospective associations among these constructs.Results The outcomes of the cross-lagged path analysis indicated the presence of significant bidirectional relationships between academic stress and physical activity, mental health history, and time management skills. In addition, bidirectional interconnections existed between physical activity and mental health history. Furthermore, unilateral correlations were detected between physical activity and time management skills.Conclusions These findings underscore the importance of an integrated approach to student health initiatives and highlight the need for comprehensive support systems that address student well-being's psychological and physical aspects.